2007
DOI: 10.1177/1527002505276716
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Attendance at Major League Baseball Spring Training Games

Abstract: This paper examines the determinants of game-day attendance during Major League Baseball's 2002 spring training season in Florida. Our model of game-day attendance includes location, quality of game, and time and weather variables. A censored Tobit estimation procedure is used to estimate our model. Our results indicate that the quality of the game, average ticket price, and several location-specific factors affect attendance. Specifically, our results suggest that changes in income have no effect on attendanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
(49 reference statements)
2
14
0
Order By: Relevance
“…In addition, in their study, Tojjari et al (2010) stated that economic factors had an important role in encouraging spectators for their presence in stadiums (20). Donihue, Findlay, and Newberry (2007) stated that an increase in the ticket price reduced the presence of spectators (21). On facility-equipment factors, Yusof, See, and Yusof (2008) emphasized the significance of facilities in stadiums and pointed out that paying more attention to these cases was essential for the managers of stadiums and acknowledged that the physical space of the stadium was of utmost importance to satisfy spectators (22).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in their study, Tojjari et al (2010) stated that economic factors had an important role in encouraging spectators for their presence in stadiums (20). Donihue, Findlay, and Newberry (2007) stated that an increase in the ticket price reduced the presence of spectators (21). On facility-equipment factors, Yusof, See, and Yusof (2008) emphasized the significance of facilities in stadiums and pointed out that paying more attention to these cases was essential for the managers of stadiums and acknowledged that the physical space of the stadium was of utmost importance to satisfy spectators (22).…”
Section: Discussionmentioning
confidence: 99%
“…A related element in professional sport economics and marketing, the demand for sports in contemporary times, including determinants of attendance to games, has also drawn significant attention (Borland & MacDonald, 2003). Indeed, many researchers have made conceptual contributions to the study of game day experience (Clemes, Brush, & Collins, 2011;Donihue, Findlay, & Newberry, 2007;Trail & James, 2001). Figure 1 provides a framework summarising these and other conceptual contributions.…”
Section: Conceptual Framework In the Study Of Sports' Consumption Anmentioning
confidence: 99%
“…The authors found that, while changes in people' incomes do not have an effect on attendance, factors such as location, average ticket prices and the quality of the game can affect people's decision to attend or to not attend a game. Moreover, as the local team's longevity in its location increases, game attendance tends to decline; in addition, attendance was found to be larger in cases where two teams co-exist in the same city (Donihue et al, 2007). Funk et al (2004) studied team sport involvement using 18 antecedents that focussed on areas related to attendance to games.…”
Section: Conceptual Framework In the Study Of Sports' Consumption Anmentioning
confidence: 99%
See 2 more Smart Citations